DETERMINATION OF INORGANIC COMPONENTS INCLUDING MINOR AND TRACE ELEMENTS IN SURMA (KOHL) FORMULATIONS (Biological Sciences - PJSIR, 2022)
Quantitative estimations of silicon dioxide, phosphate, chloride and nitrates alongwith minor and trace elementsin various Surma (Kohl) formulations have been carried out using chemical and AAS methods. Out often differentpreparations, eight were found to contain lead as major constituent (72 - 82%). The remaining two were zinc based having53 and 63% of zinc, respectively.